2004
DOI: 10.1097/01.brs.0000132510.25378.8c
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Ligamentum Flavum in Degenerative Lumbar Disease

Abstract: Various pathologic findings provided important foundations for discussing the pathogenesis of lesions in ligamentum flavum. Calcification was frequently observed in elderly patients and those with cauda equina symptoms, and these patients tended to have severer preoperative symptoms. Chondroid cells were frequently observed in patients with spondylolisthesis, and patients with ossification had a greater % slip, suggesting involvement of mechanical load in ossification of ligaments. The pathologic findings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 53 publications
5
98
2
Order By: Relevance
“…CPPD crystal deposition is occasionally observed in the cervical [11,12] or lumbar spine [13,14], but rarely in the thoracic spine [15,16]. Generally, CPPD crystal deposition in the LF has been observed in normal asymptomatic elderly individuals as one of the physiological aging processes [17,18]. However, the mechanism of CPPD crystal deposition in the present series cannot be explained simply as a physiological aging process, because the calcification was not detected on the CT scan at the time of occurrence of PJF.…”
Section: Discussioncontrasting
confidence: 44%
“…CPPD crystal deposition is occasionally observed in the cervical [11,12] or lumbar spine [13,14], but rarely in the thoracic spine [15,16]. Generally, CPPD crystal deposition in the LF has been observed in normal asymptomatic elderly individuals as one of the physiological aging processes [17,18]. However, the mechanism of CPPD crystal deposition in the present series cannot be explained simply as a physiological aging process, because the calcification was not detected on the CT scan at the time of occurrence of PJF.…”
Section: Discussioncontrasting
confidence: 44%
“…5,6 Increasing patient age has been shown to correlate with LF thickening at the L4 -5 level, 6,7 presenting as young as 30 years of age in 1 recent study 8 ; however, Safak et al 9 have recently found no such association.…”
Section: Discussionmentioning
confidence: 84%
“…With the development of imaging methods and the increased aging of society, the incidence of LSS has shown an annual increase. LSS is one of the main causes of leg pain in older individuals (1)(2)(3)(4), including intermittent claudication, numbness of buttocks and legs, activity disorder of waist and legs, muscle wasting and tendon dysreflexia (5). Intermittent claudication caused by neuropathic pain (NP) is a special chief complaint of LSS, which may be reconstructed by clinical workers; however, its mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%